2018
DOI: 10.1111/ijfs.13885
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of lipoxygenase in soybean by radio frequency treatment

Abstract: Summary Polyunsaturated fatty acids are oxidised to generate beany flavour under catalysis of lipoxygenase (LOX). Using conventional thermal treatment to inactivate LOX lead to a serious nutritional and functional loss in soybean products due to the prolonged exposure to the high‐temperature environment. Radio frequency (RF) is a different type of heating technology that sample is heated inside and outside at the same time with deep penetration. RF treatment was proposed to process soybean to rapidly inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…However, owing to the low molar absorptivity of the reaction products, the determination of low specific activity preparations is still susceptible to interference by protein absorption. This method has been widely used in recent studies of legume LOX including pea (Akyol, Alpas, & Bayındırlı, 2006;Leone et al, 2001;Szymanowska et al, 2009), mung bean seeds (Aanangi et al, 2016), and soybean and soy product (Jiang et al, 2018;Manassero, Vaudagna, Sancho, Añón, & Speroni, 2016;Tedjo, Eshtiaghi, & Knorr, 2000).…”
Section: Diene Conjugated Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, owing to the low molar absorptivity of the reaction products, the determination of low specific activity preparations is still susceptible to interference by protein absorption. This method has been widely used in recent studies of legume LOX including pea (Akyol, Alpas, & Bayındırlı, 2006;Leone et al, 2001;Szymanowska et al, 2009), mung bean seeds (Aanangi et al, 2016), and soybean and soy product (Jiang et al, 2018;Manassero, Vaudagna, Sancho, Añón, & Speroni, 2016;Tedjo, Eshtiaghi, & Knorr, 2000).…”
Section: Diene Conjugated Methodsmentioning
confidence: 99%
“…This is because RF treatment has a shorter heating time and faster thermal transmission rate. Different from traditional heating technology, RF heats the sample inside and outside simultaneously (Jiang et al, 2018 however, the same duration of conventional thermal treatment (110 C) reached only 3.08%. Moreover, the functional properties of RF-treated soybean protein isolate (SPI) were much higher than the conventional thermal-treated SPI samples.…”
Section: Radio Frequencymentioning
confidence: 98%
See 1 more Smart Citation
“…The determination of urease and trypsin inhibitor activity of soybean samples was carried out following the procedures reported by Yalcin & Basman (2015) and Li et al (2018), respectively. The LOX activity of samples was determined according to the method of Jiang et al (2018). LOX activity assay required 0.1 mL of 1:5 diluted crude enzyme solution and 3 mL of 0.2 M borate buffer at pH 9.0 containing 0.02% (v/ v) of linoleic acid and Tween 20.…”
Section: Anf Activity Determinationmentioning
confidence: 99%
“…92 RF can replace traditional hot-water blanching to inactivate LOX and PPO while maintaining the quality of a treated product. 93 Jiang et al, 94 for example, proposed that RF could be used to rapidly inactivate LOX while maintaining the quality and functional properties of soybean products. The results showed that the inactivation of LOX was 94% after 210 s of RF treatment; such an inactivation in the case of conventional heat treatment (at 110°C) was only 3%.…”
Section: Rf Inactivation Technologymentioning
confidence: 99%